S129 Does inflammation predict successful pleurodesis? a post hoc analysis from the time 1 trial. (15th November 2017) - Mercer, RM; Macready, J; Jeffries, H; Speck, N; Kanellakis, N; Maskell, N; Pepperell, J; Saba, T; Ali, N; West, A; Miller, RF; Asciak, R; et al.
Abstract : Introduction: Malignant pleural effusions are a common complication of advanced malignancy, have a poor prognosis and have a significant impact on quality of life. Treatment strategies include chest drain and pleurodesis, or insertion of an indwelling pleural catheter. Successful pleurodesis is thought to be due to the body's inflammatory response resulting in pleural symphysis. This post hoc analysis of data from the TIME 1 was conducted to address assess whether there is a correlation between the pleurodesis and a systemic inflammatory response. Methods: A total of 282 patients from the TIME 1 trial had data on pleurodesis success, which was defined as no further pleural procedures for up to 3 months after pleurodesis. Patients who had undergone thoracosopy and poudrage as well as those who had undergone chest drain with pleurodesis were included. Sterile talc was used in all patients. The difference in the white cell count (WCC) and C-reactive protein (CRP) levels was calculated between the day of pleurodesis (Day 0) and Day 1. The data are normally distributed thus independent t test was used for analysis. The CRP Day 0 and 1 data were not normally distributed, and therefore were log transformed to produce a normal distribution. Results: Two hundred and eighty two patients were included in the analysis with a mean age of 71 in both groups. 229 had a successful pleurodesis and 53 patients required a further pleural procedure on the ipsilateral side signifying failed pleurodesis. 193 patients had CRP levels and 220 patients had WCC levels recorded on both Day 0 and Day 1. Patients who had a successful pleurodesis had a significantly greater rise in CRP than those who failed pleurodesis. There was no significant difference in the change in WCC between the groups. There was also no significant difference in Day 0 and Day 1 WCC or CRP levels between the two groups. Conclusions: This analysis demonstrates that systemic rise in CRP as an indicator of inflammation is a better predictor of pleurodesis success than the WCC. These data support the hypothesis that higher levels of inflammation are associated with pleurodesis success.